2005
DOI: 10.1128/mcb.25.13.5339-5354.2005
|View full text |Cite
|
Sign up to set email alerts
|

Subunits of the Heterotrimeric Transcription Factor NF-Y Are Imported into the Nucleus by Distinct Pathways Involving Importin β and Importin 13

Abstract: The transcriptional activator NF-Y is a heterotrimeric complex composed of NF-YA, NF-YB, and NF-YC, which specifically binds the CCAAT consensus present in about 30% of eukaryotic promoters. All three subunits contain evolutionarily conserved core regions, which comprise a histone fold motif (HFM) in the case of NF-YB and NF-YC. Our results of in vitro binding studies and nuclear import assays reveal two different transport mechanisms for NF-Y subunits. While NF-YA is imported by an importin ␤-mediated pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
87
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 84 publications
7
87
0
5
Order By: Relevance
“…Additionally, the affinity of importin 13 to the NC2 complex might be low in vivo due to phosphorylation of the NC2 subunits (3). As recently described for its closest relative, the NF-YB/NF-YC histone-fold heterodimer, only the dimerized NC2 subunits were recognized by importin 13 (52). Hence, despite their functional divergence these two histone-fold heterodimers rely on the same import mechanism to translocate through the NPC.…”
Section: Nc2␣ (mentioning
confidence: 73%
See 1 more Smart Citation
“…Additionally, the affinity of importin 13 to the NC2 complex might be low in vivo due to phosphorylation of the NC2 subunits (3). As recently described for its closest relative, the NF-YB/NF-YC histone-fold heterodimer, only the dimerized NC2 subunits were recognized by importin 13 (52). Hence, despite their functional divergence these two histone-fold heterodimers rely on the same import mechanism to translocate through the NPC.…”
Section: Nc2␣ (mentioning
confidence: 73%
“…In that way, the NC2 complex behaves like its closest relative, the NF-YB/NF-YC histone-fold heterodimer. Only the heterodimerized NF-YB/NF-YC subunits were specifically recognized by importin 13, as shown previously (52). Because heterodimerization of both NC2␣ with NC2␤ and NF-YB with NF-YC is a prerequisite for importin 13 binding, the minimal sequence elements recognized by importin 13 comprise the histone-fold domains of both NC2 subunits.…”
mentioning
confidence: 71%
“…which normally resides in the cytoplasm, rapidly translocates to the nucleus through a dual mechanism where NF-YA is transported in an importin h-dependent pathway, whereas the NF-YB and NF-YC subunits are translocated through a distinct pathway involving importin 13 (44). Our investigation of all three NF-Y subunits in response to cisplatin and radiation showed an increase in NF-YA and NF-YB transcript levels beginning at 8 h reaching maximal levels 48 h posttreatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…7) where, upon stress treatment with cisplatin and radiation, NF-Y localizes to the nucleus (44) and transcriptionally activates the expression of the EBV lytic genes BRLF1 and BZLF1 within 30 min. NF-Y activation of BRLF1 may be mediated by the physical interaction of NF-Y with one or a combination of the three consensus sequences within the distal promoter region.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of histone fold motifs in the NF-YB and NF-YC implicates these proteins as being likely to have multiple protein-protein interactions with other transcription factors as well as being given protein modifications. The NF-YA and NF-YB/NF-YC heterodimer were shown to be separately imported to the nucleus through Importins ␤ and 13, respectively (36). However, our coimmunoprecipitation and ChIP assays showed that NF-YC alone, not a complex of NF-YA, NF-YB, and NF-YC, is recruited to a MR-responsive ENaC gene promoter, thus resulting in MR-mediated transcriptional repression.…”
Section: Discussionmentioning
confidence: 48%